Can we align antibiotic policies at an international level in the absence of harmonized definitions?. (14th January 2022) - Simjee, Shabbir; Henninger, Marc; Ippolito, Gabriella; Atkinson, Jackie
Abstract: The foundations of robust policies are reliant on harmonized definitions allowing consistency of understanding. However, it is evident that there is a lack of harmonization of definitions in the antibiotic space and even the simplest of terms such as 'antibiotic' and 'antimicrobial' do not have a single harmonized definition at an international level. This lack of harmonization makes interpretation of policies in different geographies a difficult, sometimes impossible, task. This article proposes a set of definitions that could be adopted by international institutions such as the WHO, World Organisation for Animal Health (OIE) and Food and Agriculture Organisation (FAO) as well as regulatory agencies.